227k views
5 votes
5 (2x – 1) –7 = 2 (x – 3)

1 Answer

1 vote

Answer:

x−3=x−3

Explanation:

Evaluate (2x−1)−7, then set it equal to 2.

Subtract 7 from −1 = 2x−8

Solve 2x−8=2.

Move all terms not containing x to the right side of the equation.

Add 8 to both sides of the equation=2x=2+8

Add 2 and 8=2x=10

Divide each term by 2 and simplify.

Divide each term in 2x=10 by 2=2x/2=10/2

Cancel the common factor of 2

Cancel the common factor=10/2

Divide x by 1=x=10/2

Divide 10 by 2=x=5

Remove parentheses=x−3

List all of the solutions.

5=

(2x−1)−7=2=x=5

x−3=x−3

User Nikita Kuznetsov
by
4.7k points